Inhibition of Fusarium oxysporum growth in banana by silver nanoparticles: In vitro and in vivo assays; PLoS One; Vol. 20, iss. 2 - Mendoza N. V. Natalia Veronica; Yanez P. Paola; Magdama F. Freddy; Pacheco R. Ricardo; Vielma J. Joel; Vanegas M. E. Maria Eulalia; Bogdanchikova N. Nina; Pestryakov A. N. Aleksey Nikolaevich; Chong P. Pablo (2025, 2025)
Title screen